Psychometric Properties of the Pittsburgh Sleep Quality Index (PSQI) in a Cohort of Peruvian Pregnant Women. - Zhong, Qiu-Yue (2015)
STUDY OBJECTIVES: We sought to evaluate the construct validity and factor structure of the Spanish-language version of the Pittsburgh Sleep Quality Index (PSQI) among pregnant Peruvian women. METHODS: A cohort of 642 women were interviewed at ≤ 16 weeks of gestation. During interview, we ascertained information about lifestyles, demographics, sleep characteristics, and mood symptoms. Stress induced sleep disturbance, depressive symptoms, and anxiety symptoms were evaluated using the Ford Insomnia Response to Stress Test (FIRST), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) assessment scales, respectively. Consistency indices, exploratory and confirmatory factor analyses, correlations, and logistic regressions were used. RESULTS: Both exploratory and confirmatory factor analyses indicated a three-factor solution: sleep quality, sleep efficiency, and sleep medication. We observed significantly positive correlations of the PSQI with the FIRST (0.42), the PHQ-9 (0.49), and the GAD-7 (0.46). Poor sleepers (PSQI global score > 5) had significantly increased odds of experiencing stress-induced sleep disturbance (odds ratio, OR = 3.57; 95% CI: 2.40, 5.31), depression (OR = 5.48; 95% CI: 3.58, 8.37), and generalized anxiety disorder (OR = 4.57; 95% CI: 3.08, 6.76). CONCLUSION: The Spanish-language version of the PSQI instrument was found to have good construct validity among pregnant Peruvian women. Consistent with some other studies, the PSQI was found to have a three-factor structure. Further assessment and validation studies are needed to determine whether the three, factor-specific scoring of the PSQI is favored over the PSQI global score in diverse populations.